ETL Implementation with Pentaho for Sales Data Visualization: A Case Study of Lunabit Beauty Bar - I Gde Eka Dharsika; Ni Kadek Ayu Sulistiawati; Ida Bagus Gede Sarasvananda (CV. Digital Innovation, 2025)
The rapid growth of information technology has encouraged businesses to optimize their data management through data warehousing and visualization. This study presents the implementation of the Extract, Transform, Load (ETL) process using Pentaho Data Integration (PDI) for the development of a sales data visualization dashboard at Lunabit Beauty Bar. The ETL process was carried out on sales transaction data originally stored in CSV format and later structured into a MySQL-based data warehouse. The stages of ETL include data extraction, transformation involving cleaning, integration, and validation to ensure consistency, and loading into the warehouse for further analysis. The visualization dashboard displays several analytical perspectives, including sales trends over time, sales performance by treatment, customer contributions, and treatment ranking from highest to lowest. To evaluate system performance and usability, a User Acceptance Test (UAT) was conducted involving 16 respondents, including the owner and staff. The results showed a satisfaction rate of 94%, indicating that the system met the company's needs in providing valid, clear, and easy-to-understand information. This research demonstrates that the integration of ETL processes with data visualization tools can support business decision-making, particularly in monitoring sales performance and designing promotional strategies.